STUDI ANGGREK EPIFIT PADA TIGA LOKASI DI KABUPATEN MALINAU, KALIMANTAN TIMUR - Tirta, I Gede; Lugrayasa, I Nyoman; Irawati, Irawati (Buletin Kebun Raya, 2010)
A study on epiphytic orchids in three locations (Senturan Forest, Mount Sidi and Mount Jarang) in Malinau District showed that most epiphytic orchids were found in location with moderate light intensity rather than in low and high light intensities. Many orchids were found on parts of trees covered by thin mosses rather than on thick mosses. Three hundred and seventy one orchid specimens were collected from the three locations and at least 71 specimens were new collections to Eka Karya Botanic Garden, Bedugul.